Magnetic MXene/g-C3N4 nano catalyst for photocatalytic degradation of clindamycin contaminate in wastewater - Hadeel A. Abbas; Khalid K. Abbas; Ahmed M.H. Abdulkadhim Al-Ghaban (Results in Chemistry)
The increasing concerns surrounding micropollutant contamination necessitate urgent and effective strategies for their elimination. Several stages explored the photocatalytic degradation of pharmaceutical contaminants in wastewater using novel magnetic g-C3N4/MXene nano photocatalysts are synthesized in this work. The surface chemistry, morphology, crystallinity, surface area, and propensity to participate in electron transfer reactions of the g-C3N4/MXene nano were characterized using a set of analytical measurements. These analyses confirmed the successful formation of a unique complex with ferromagnetic properties conferred by incorporating Fe3O4. After 120 min of sunlight exposure, the g-C3N4/MXene magnetic catalyst showed a superior reduction of 92 % of clindamycin in real wastewater. High organic carbon removal of > 38 % was also observed after the 2 h period. The study also observed the stability of the catalyst over four cycles, maintaining a removal level of > 58 %, highlighting its potential applications in water treatment processes by increasing the interlayer spacing, g-C3N4, and MXene combined to produce an excellent surface area with more active sites on their surface, which enhanced the transfer of electron/hole pairs and provided excellent degradation capacity.